CS-12 IDH-1 MUTANT GLIOMA IN BROTHER AND SISTER, ONSET AT AGE OF 30s. (16th December 2019) - Kitai, Ryuhei; Yamauchi, Takahiro; Neishi, Hiroyuki; Isozaki, Makoto; Tsunetoshi, Kenzo; Matsuda, Ken; Arishima, Hidetaka; Kodera, Toshiaki; Kikuta, Ken-ichiro
Abstract: A 38-year-old man consulted with our neurosurgery group at University of Fukui hospital, due to tonic-clonic seizures. An MRI revealed a non-enhanced intra-axial tumor at the left frontal lobe. CT showed no calcification in the tumor. The tumor was removed by awake brain surgery. The pathological specimen was diagnosed as a diffuse astrocytoma with IDH-mutant. Immunohistochemical staining and DNA sequencing confirmed a R132H mutation at IDH-1. Telomerase Reverse Transcriptase (TERT) promoter mutation and 1p 19q codeletion was not evident. Four years later, his sister, a 40-year-old woman, had an MRI as a routine medical check that found a right frontal tumor at the mirror site of her brother's tumor, and with identical radiological findings. The tumor was completely removed. The specimen revealed oligodendrocytoma, with mutant IDH and 1p/19q co-deleted. DNA sequencing showed also R132H at IDH-1. TERT promoter mutation was evident at C228T, which is a surrogate marker for oligodendroglioma. IDH-mutant astrocytoma and oligodendroglioma in siblings; and germline mutation of IDH have not been reported. However, the respective incidences of astrocytoma and oligodendroglioma are 0.55/100, 000/year and 0.26/100, 000/year according to United State statistics, which indicates that merely coincidental occurrence of these tumors is extremely unlikely. A trigger for IDH mutation that runs in rare families could warrant whole-genome sequencing.